MULTIAGENT TECHNOLOGIES’ METHOD IN MANAGING BUSINESS-PROCESSES OF THE TECHNICAL PREPARING FOR PRODUCTION - Pavlenko, P.N. (Proceedings of National Aviation University (archive), 2005)
The method of managing the process of the extended productions technological preparation is given. The method is used for integrating the automated systems of industrial assignment of CAD/CAM/SAPP and ERP systems.